An innovative vegetation survey design in Mediterranean cliffs shows evidence of higher tolerance of specialized rock plants to rock climbing activity. Issue 2 (7th January 2018) - March‐Salas, Martí; Moreno‐Moya, Miguel; Palomar, Gemma; Tejero‐Ibarra, Pablo; Haeuser, Emily; Pertierra, Luis R.
Abstract: Questions: Is rock climbing pressure, together with microtopographic conditions, disturbing cliff plant cover and composition? What are the climbing impacts on rock specialist and non‐specialist species? Can a case‐control approach, not previously implemented in cliff environments, offer additional value for actual and long‐term ecological research? Location: Chulilla, Levante coast, Spain. Methods: We surveyed in situ nine rock climbing routes in order to examine differences in plant species richness and vegetation cover between unclimbed and climbed transects. To evaluate the effect of rock climbing on vegetation, we implemented a case‐control methodology using the two zones immediately adjacent to common climbing routes as control points (i.e. unclimbed transects). Three quadrats of 3 m × 3 m were established at different cliff heights. All identified species were categorized as either specialized rock species or non‐specialized rock species based on their habitat preferences from literature. Non‐specialized rock species were further differentiated as either moderately associated with rocky environments or strict generalists. The rock climbing impact on each group of species was analysed using LMM. Results: Our results provide evidence of the effects of rock climbing on a Mediterranean cliff, which has received little attention so far. Significantly fewer generalist species were present on climbed compared to unclimbed transects, while specialized and moderately specialized rock species were not significantly affected by rock climbing intensity. Furthermore, while rock‐specific and moderately specialized species could cope with microsite heterogeneity, areas with fewer cracks had significantly negative effects on generalist species. Conclusions: Moderate rock climbing activity on cliff environments might not reduce the presence of specialized rock‐dwelling species; however, this activity inherently impacts the biodiversity of cliff ecosystems due to its large effect on generalist species. We recommend that future conservation studies account for the degree of species dependence on rocky habitats to better understand rock‐climbing impacts in these singular ecosystems. According to our experience, the implementation of an adjacent case‐control survey design for monitoring cliff vegetation can help improve and unify methodology for such studies, as this is still an underdeveloped field. Abstract : The effects of rock‐climbing on plants thriving in cliff ecosystems are poorly known. Furthermore, the roles of several relevant features are vastly unexplored. To examine these issues, a new methodology was implemented while surveying Mediterranean cliffs, one of the least studied habitats. Among other results, rock‐specialist species had notably higher resistance to the climbing impact while generalist were more disturbed.